Respuesta :

Answer

Y= 3 × 2 + 6x + 1 = 6 + 6x +1 = 6x + (6+1) = 6x + 7

Answer:

This is a function, so the answer is a plot, you can see it in the attached picture

Step-by-step explanation:

This is a function, the best way to go here is to graph.

First lest find the roots of 3x2+6x+1, you do this by using the quadratic equation

[tex]x_{1} = \frac{-b + \sqrt{b^{2}-4ac }}{2a}\\x_{2} = \frac{-b - \sqrt{b^{2}-4ac }}{2a}[/tex]

Where a=3, b=6, c=1

Using that, you get, x1 = -1 - sqrt(2/3) which is a negative number, and x2=sqrt(2/3) - 1 which is a negative number.

These number represent values that makes the function equals =0

Now if we make x=0, the result is y=1,

We have a better idea of what is to plot and it is shown on the attached picture

Ver imagen Gasaqui